Analisis Penanaman Sikap Sosial Peserta Didik Melalui Pembelajaran Ilmu Pengetahuan Sosial Kelas III SD Negeri Winong 01 Kabupaten Pati - Anindita, Rizki Dwi; Wardana, M. Yusuf Setia; Purnamasari, Iin (CV. Supernova Office Stationary and Printing, 2023)
In the world of formal education today, there are problems that arise due to the increasing number of impacts that can affect the development of students' social attitudes. Teachers can use social studies learning to instill the value of social attitudes in students as a solution. The problem in this study is the analysis of inculcating students' social attitudes through learning Social Sciences in the third grade of SD Negeri Winong 01. The research used in this research is a qualitative research method with a descriptive approach. Data collection techniques used are: observation, interviews, questionnaires, and documentation. Based on the results of interviews, observations, and questionnaires that have been carried out during the research, it was found that at SD Negeri Winong 01 the role played by the teacher in instilling social attitudes of students through learning Social Sciences class, namely the teacher has shown a role in instilling an attitude of honesty, courtesy , tolerance, self-discipline, helping students through social studies learning. In the process of cultivating students' social attitudes through social studies learning, teachers still find obstacles to indicators of honesty and self-discipline, such as students still cheating while doing assignments and there are still some students who don't want to do picket assignments. However, the researcher assessed that the overall social attitude of the third grade students was good.